An investigation of knowledge creation process in the learningzone learning management system amongst postgraduate students - Ahmad, Mazida; Husain, Adzira; Zulkifli, Abdul Nasir; Faisal Mohamed, Nur Fadziana; A. Wahab, Syamila Zakiah; Md Saman, Azmi; Yaakub, Abdul Razak (2011)
Knowledge management (KM) has been discussed in various domain but less emphasis is given in the educational field particularly in understanding the interaction between tacit and explicit knowledge.The knowledge is formed through connection of online learning environment elements.Therefore, the outcome of KM in educational field is unknown due to insignificant attention towards knowledge created from the process itself. This paper discusses the process of knowledge creation based on the Socialization, Externalization, Combination and Internalization (SECI) model amongst postgraduate students in an online learning environment.Research sample covers 160 postgraduate students who were actively involved in Learning Management System (LMS) support environment.A research instrument has been developed based on the SECI constructs. Factors examined are the intensity of knowledge creation processes for transforming tacit knowledge in the learning, thinking and decision making skills.The findings show that the model fit the data for thinking and decision making skills only.The findings indicate that the model is not applicable for developing learning skill for postgraduate students.